Scientific Opinion on the request from the USA regarding export of Florida citrus fruit to the EU (EFSA journal, 2011)
Following a request from the EU Commission, the EFSA PLH Panel conducted a scientific opinion on risk analysis and supporting documents provided by APHIS/USDA in support of the request to remove the Union's plant health import requirement that citrus fruit imported into the EU be sourced from groves where, since the beginning of the last cycle of vegetation no symptoms of citrus canker were observed, neither in their vicinities. The PHL Panel concluded that the transmission of Xanthomonas citri subsp. citri (Xcc) on asymptomatic citrus fruit was more likely when the fruit were collected from infested than from non‐infested areas and groves. Symptomatic fruit carries more Xcc cells than asymptomatic fruit and the packinghouse disinfectant treatments do not achieve the eradication of Xcc. The application of management option 2 (i.e. ‘allow distribution of all types and varieties of commercially packed citrus fruit to all US States, subject to packinghouse treatment with APHIS‐approved disinfectant. No packinghouse phytosanitary inspection is required’) selected by USDA will result in an increase in the Xcc load of citrus fruit consignments and in a subsequent increase in the probability of spread of citrus canker through the fruit pathway. Some data provided in the APHIS‐USDA documents support that citrus fruit remain a conceptually possible pathway for transmitting and establishing citrus canker disease. The PLH Panel agrees that transmission of Xcc from infected fruit to a susceptible host is rare. But the withdrawal of the current EU requirement that citrus fruit imported into the EU be sourced from groves where no symptoms of citrus canker have been observed in the field of production and in its immediate vicinity since the beginning of the last cycle of vegetation, will increase the probability of introduction of Xcc into new areas.